Impact of obesity and gender on the progression of hip and knee osteoarthrosis: An epidemiological study in the general population - Žani Banjanin; Janja Bojanić; Jadranka Pešević Pajčin; Radmila Ubović; Nina Rodić Vukmir (Биомедицинска истраживања, 2013)
Introduction: . Obesity is one of the most important risk factors for osteoarthritis (OA) of the knee. However, notwithstanding numerous studies on this topic, the link between obesity and OA of the hip and between OA and gender is still not clear enough. The aim of the study was to investigate the asso ciation between obesity, gender and degenerative joint disease of hip and knee within adult population of the municipality of Laktaši. Methods: . The study included a retrospective analysis of a total of 5301 patients aged between 18 and 91, treated for osteoarthritis of the spine, hip and knee during the period from January 1st 2005 to September 15th 2010. Out of 7089 OA of spine, hip and knee, 1169 were OA of the hip and knee. Diagnosis of OA was based on clinical symptoms, physical examination and X-rays (78% of patients). Results: . Out of 7089 spine, hip and knee OA, 1169 were hip and knee OA. Percentage of hip OA was 5.8% (67.9% in women and 32.1% in men). Percentage of knee OA was 10.7% (66.1% in women and 33.9% in men). Among participants with Body Mass Index (BMI) above 30, 22.1% of them were with knee and hip OA. Percentage of hip OA was 6.7% (67.5% in women and 32.5% in men). Percentage of knee OA was 15.4% (72.4% in women and 27.6% in men). It was noticeable that there was a considerable statistical significance (p<0.01) of the association between obesity and knee OA, whilst there was no statistically significant (p>0.05) link between obesity and hip OA. Conclusion: . A high BMI was significantly associated with knee OA, but not with hip OA. A significant increase in the prevalence of arthritis was observed in women during menopause.
Keywords: osteoarthritis; knee; hip; gender; obesity